Hepatic resection, hepatic arterial infusion pump therapy, and genetic biomarkers in the management of hepatic metastases from colorectal cancer - McAuliffe, John C.; Qadan, Motaz; D’Angelica, Michael I. (Journal of Gastrointestinal Oncology; Vol 6, No 6 (December 01, 2015): Journal of Gastrointestinal Oncology (Applying Tumor Genotyping and New Clinical Approaches to the Management of Colorectal Cancer), 2015)
The liver is the most common site of colorectal cancer metastasis. Fortunately, improvements have been made in the care of patients with colorectal liver metastasis (CRLM). Effective management of CRLM requires a multidisciplinary approach that is tailored to individuals in order to achieve long-term survival, and cure. Resection and systemic chemotherapy provides benefit in selected individuals. An adjunct to resection and/or systemic chemotherapy is the use of hepatic arterial infusion pump (HAIP) therapy. Many studies show HAIP provides benefit for select patients with CRLM. Added to the crucible of a multidisciplinary approach to managing CRLM is the ever growing understanding of tumor biology and genetic profiling. In this review, we discuss the outcomes of resection, systemic therapies and HAIP therapy for CRLM. We also discuss the impact of recent advances in genetic profiling and mutational analysis, namely mutation of KRAS and BRAF, for this disease.